Alpha-Actinin-3 (ACTN3) R577X Polymorphism on Brain-derived Neurotrophic Factor (BDNF) Levels of Pre- and Post-Eccentric Exercised Male Subjects - Audira Syafana Khadijah; Aurel Aryati; Aurel Diffa Arpy; Angela Excellcia Larasaty Susetyo; Monica Dwi Hartanti (The Prodia Education and Research Institute (PERI), 2025)
BACKGROUND: Eccentric exercise, characterized by muscle lengthening underload, elicits physiological responses, including alterations in brain-derived neurotrophic factor (BDNF) levels, crucial for neuroplasticity and exercise adaptations. The Alpha-Actinin-3 (ACTN3) gene encodes α-actinin-3, a protein in fast-twitch muscle fibers associated with explosive performance. The R577X polymorphism in ACTN3 is associated with athletic performance, particularly in power-based activities. However, its influence on the BDNF response to eccentric exercise remains unclear. This study investigated whether the ACTN3 R577X polymorphism modulates BDNF levels post-exercise.METHODS: Male subjects aged 18-30 years old, who were not involved in structured physical activity, and abstaining from alcohol and protein supplements within specified periods, were involved in this study. Subjects’ genotypes were identified using polymerase chain reaction (PCR) and classified into different ACTN3 genotypes (RR, RX, XX). All subjects underwent an eccentric exercise protocol. BDNF levels were measured pre-exercise, post-exercise, and 72 hours post-exercise using sandwich Enzyme-Linked Immunosorbent Assay (ELISA).RESULTS: Most of subjects had RX genotype (52.2%), followed by XX (39.1%) and RR genotypes (8.7%), respectively. BDNF levels decreased significantly across all time points. The RR genotype showed a decrease from approximately 270 pg/mL to 230 pg/mL, while RX and XX genotypes showed similar patterns of reduction. No significant differences in BDNF levels were observed between genotypes at any time point.CONCLUSION: Eccentric exercise leads to a consistent decrease in BDNF levels, with no significant modulation by ACTN3 genotype. These findings suggest a uniform response to exercise-induced stress across genotypes.KEYWORDS: ACTN3, BDNF, eccentric exercises, genotype, adaptation